The effect and mechanism of traditional Chinese exercise for chronic low back pain in middle-aged and elderly patients: A systematic review - Wang, Xue-Qiang; Xiong, Huan-Yu; Du, Shu-Hao; Yang, Qi-Hao; Hu, Li (Frontiers in Aging Neuroscience, 2022)
Background Increasing lines of evidence indicate that traditional Chinese exercise (TCE) has potential benefits in improving chronic low back pain (CLBP) symptoms. To assess the clinical efficacy of TCE in the treatment of CLBP, we performed a systematic review of existing randomized controlled trials (RCTs) of CLBP and summarized the neural mechanisms underlying TCE in the treatment of CLBP. Methods A systematic search was conducted in four electronic databases: PubMed, Embase, the Cochrane Library, and EBSCO from January 1991 to March 2022. The quality of all included RCTs was evaluated by the Physiotherapy Evidence Database Scale (PEDro). The primary outcomes included pain severity and pain-related disability. Results A total of 11 RCTs with 1,256 middle-aged and elderly patients with CLBP were included. The quality of all 11 included RCTs ranged from moderate to high according to PEDro. Results suggested that TCE could considerably reduce pain intensity in patients with CLBP. Overall, most studies did not find any difference in secondary outcomes (quality of life, depression, and sleep quality). Conclusion The neurophysiological mechanism of TCE for treating CLBP could be linked to meditation and breathing, posture control, strength and flexibility training, and regulation of pain-related brain networks. Our systematic review showed that TCE appears to be effective in alleviating pain in patients with CLBP.